Exact solutions of the navier stokes equations - 497695 Noor Fadiya Mohd Noor; Norsarahaida S. Amin, Supervisor; Fakulti Sains (2006)
Thesis (Sarjana Sains (Matematik)) - Universiti Teknologi Malaysia, 2006